Stem and Covid-19 - Hansen, Grace (Coronavirus (Abdo Kids), 2021)
This title takes a look at some of the amazing medicine and technology being created (like a COVID-19 vaccine and antibody therapy) and being utilized (like drones and ventilators) to help in the fight against COVID-19. This book shows the incredible things that scientist and engineers can accomplish when faced with a problem as big as a pandemic. Complete with inviting photos and images (labeled when needed), bolded glossary terms, and more.